Bifurcations and Single Peak Solitary Wave Solutions of an Integrable Nonlinear Wave Equation (Advances in Applied Mathematics and Mechanics, 2021)
Dynamical system theory is applied to the integrable nonlinear wave equation $u_t±(u^3−u^2)x+(u^3)xxx=0$. We obtain the single peak solitary wave solutions andcompacton solutions of the equation. Regular compacton solution of the equation corresponds to the case of wave speed $c$=0. In the case of $c^6$≠0, we find smooth solitonsolutions. The influence of parameters of the traveling wave solutions is explored byusing the phase portrait analytical technique. Asymptotic analysis and numerical simulationsare provided for these soliton solutions of the nonlinear wave equation.